Effect of Marketing Mix on Consumer Purchase Decisions to Buy Cavendish Banana at Modern Markets in Semarang - Titik Ekowati; Tutik Istiqomatin; Agus Setiadi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2021)
This study aims at identifying marketing mix of purchase decisions to buy Cavendish banana and analyzing the effect of marketing mix on purchase decisions to buy Cavendish banana at modern market in Semarang. This research was conducted at modern market in Semarang, namely Gelael Supermarket, Ada Swalayan, Superindo and Giant. Survey was employed as research method in this study. 100 respondents were taken for research sampling. The independent variables used were products, prices, places, and promotions, while the dependent variable was decisions. Descriptive analysis having been conducted shows that the variables of product have an average of 4.14; a variable of price is 3.65; a variable of place is 4.32, a variable of promotion is 3.26; and a variable of purchase decision is 3.85. Statistical analysis having been carried out shows that the f-test of product, price, place and promotion variables simultaneously affect the consumer purchase decision to buy Cavendish bananas with an f-count value of 26.378. Besides, the results of the t-test of product, price and promotion variables partially affect the consumer purchase decision to buy Cavendish bananas with t-count value of 1.984. Moreover, the place variable does not partially affect the consumer purchase decision to buy at Modern Market in Semarang.